A micro magnetically controlled robot and its preparation method and application
By using loose porous MOFs films formed by metal oxides and organic ligands in micro magnetron robots, combining magnetic and non-magnetic metal layers, the problems of low carrying efficiency and insufficient adaptability of existing micro magnetron robots are solved, and the problem of low loading efficiency and insufficient adaptability of existing micro magnetron robots is achieved. Adaptability of efficient drug delivery and complex applications.
Patent Information
- Application Number
- CN202110712174.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-06-25
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2041-06-25
AI Technical Summary
Existing micro magnetron robots have low carrying efficiency in complex applications and are not adaptable to complex applications.
Using loose porous metal organic framework layers (MOFs) formed by metal oxides and organic ligands through coordination reactions, combining magnetic metal layers and non-magnetic metal layers, miniature magnetron robots are prepared through hydrothermal reactions to form high specific surface area MOFs membranes are used to improve loading efficiency and adapt to complex applications.
It has achieved improvement in drug delivery efficiency and can effectively adapt to complex applications. By selecting different solvent combinations and ratios, the crystal structure and nitrogen content of the micro magnetron robot are adjusted to improve drug delivery efficiency.
Smart Images

Figure CN113305810B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of medical devices, and in particular to a micro magnetically controlled robot and a preparation method and application thereof. Background Art
[0002] Magnetic micro / nanorobotics can enter and carry drugs to hard-to-reach places. In actual work, magnetic fields can provide remote real-time control signals for micro / nanorobotics and achieve precise transportation of payloads through remote control. In addition, magnetic fields have minimal health risks, so wireless control through magnetic actuation is suitable for in vivo applications such as drug delivery and non-invasive surgery.
[0003] CN111493973A discloses a micro-magnetic control robot, which includes a magnetic composite spherical inner core, which can achieve periodic reciprocating vibration under the action of a pulsed magnetic field, and a flexible multi-thorny functional film, which is coated and bonded to the outer surface of the magnetic composite spherical inner core, and a plurality of thorn-like structures are distributed on the surface of the flexible multi-thorny functional film. The micro-magnetic control robot disclosed in the invention can achieve non-invasive targeted treatment of diseases such as gallstones, with obvious treatment effect, high safety, and broad application prospects. The micro-magnetic control robot disclosed in the invention provides a preparation method of a flexible multi-thorny functional film, a magnetic composite spherical inner core, and a micro-magnetic control robot, and the preparation method is simple and the production cost is low. However, the micro-magnetic control robot disclosed in the invention is not adaptable to complex applications.
[0004] CN111921072A discloses a micro-magnetic controlled robot for targeted drug delivery that mimics T4 bacteriophage and a control method thereof. The disclosed micro-magnetic controlled robot includes a robot transport capsule, a positioning and extraction magnetic field supply device, an oscillating magnetic field supply device, and a plurality of micro-robots placed in the robot transport capsule; the disclosed micro-robot includes a head shell, a medicine capsule, a tail wire trigger switch, a tail warp, a tail wire, and a control switch. The disclosed micro-magnetic controlled robot can achieve precise and targeted drug delivery in the human body, and the drug delivery speed is controllable, and multiple drugs can be delivered simultaneously. However, the disclosed magnetic controlled robot is a carrying type magnetic controlled robot, and the carrying efficiency is relatively low.
[0005] In summary, it is crucial to develop a micro magnetically controlled robot with high carrying efficiency and capable of handling complex applications. Summary of the invention
[0006] In view of the deficiencies in the prior art, the object of the present invention is to provide a micro-magnetic controlled robot and a preparation method and application thereof, wherein the micro-magnetic controlled robot can carry drugs by adsorption with high carrying efficiency and can achieve effective adaptability to complex applications.
[0007] To achieve this object, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a micro-magnetic control robot, the micro-magnetic control robot comprising a metal oxide layer, a magnetic metal layer and a metal organic framework layer (MOFs) stacked in sequence;
[0009] The metal organic framework layer is obtained by coordination reaction between metal oxide and organic ligand.
[0010] The micro-magnetically controlled robot described in the present invention uses metal oxides and organic ligands to form loose and porous MOFs through coordination reactions. Compared with the prior art that can only form powdered metal-organic frameworks using metal salts and organic ligands, the present invention uses metal oxides and organic ligands to form loose and porous granular MOFs, which not only avoids the instability of the magnetically controlled robot in the process of transporting drugs by means of a carrying method, but also greatly improves the transportation efficiency due to the porous surface of the MOFs membrane and the large specific surface area.
[0011] Preferably, the metal oxide comprises zinc oxide (ZnO).
[0012] Preferably, the organic ligand comprises 2-methylimidazole.
[0013] In the present invention, the MOFs are preferably obtained using ZnO and 2-methylimidazole as raw materials. The formed MOFs have a large specific surface area and high drug transport efficiency.
[0014] Preferably, the magnetic metal layer includes any one of nickel (Ni), cobalt, samarium cobalt, ferrosoferric oxide or neodymium iron boron, or a combination of at least two thereof.
[0015] Preferably, non-magnetic metal layers are provided on both sides of the magnetic metal layer.
[0016] Preferably, the non-magnetic metal layer includes an aluminum layer (Al).
[0017] The magnetic metal layer serves as the internal driving force for the magnetic drive of the microrobot, and the non-magnetic metal layer serves as a protective layer to prevent the magnetic metal layer from being oxidized and a reactant layer for synthesizing MOFs.
[0018] In a second aspect, the present invention provides a method for preparing the micro-magnetically controlled robot according to the first aspect, the method comprising the following steps:
[0019] (1) coating a first metal oxide layer, a first non-magnetic metal layer, a magnetic metal layer, a second non-magnetic metal layer, and a second metal oxide layer on the surface of a substrate in sequence to obtain a metal oxide surface-modified micro-magnetic robot coated on the surface of the substrate;
[0020] (2) The metal oxide surface modified micro-magnetic robot coated on the substrate surface is subjected to a heating treatment, and after cooling, it is immersed in an organic ligand solution for a hydrothermal reaction to obtain a micro-magnetic robot coated on the substrate surface, and then the micro-magnetic robot is separated from the substrate surface and post-processed to obtain the micro-magnetic robot.
[0021] In the above preparation method, the metal oxide in the second metal oxide layer undergoes a coordination reaction with the organic ligand to form a metal organic skeleton layer, which covers the upper surface of the magnetic metal layer.
[0022] Preferably, the thickness of the metal oxide layer is greater than 25 nm, for example, 50 nm, 100 nm, 150 nm, 200 nm, 250 nm, etc.
[0023] The thickness of the metal oxide layer of the present invention is greater than 25nm to ensure that the reaction with the organic ligand occurs effectively. The thickness of the metal oxide layer refers to the thickness of the upper or lower surface of the magnetic metal layer of the micro-magnetic robot before the coordination reaction with the organic ligand.
[0024] Preferably, the coating in step (1) comprises any one of electron beam evaporation, magnetron sputtering evaporation, electrochemical deposition, thermal evaporation or atomic deposition coating.
[0025] Preferably, the upper surface of the substrate in step (1) is coated with a two-dimensional pattern robot.
[0026] Preferably, the preparation method of the two-dimensional pattern robot includes coating ultraviolet photoresist or electron beam resist on the photolithography substrate before coating, then exposing the robot to ultraviolet light or electron beam according to the structure of the micro magnetron robot, and finally developing it in ultraviolet photolithography stripping solution or electron beam etchant solution to obtain the two-dimensional pattern robot.
[0027] When ultraviolet photoresist is coated on the photolithography substrate, ultraviolet rays and ultraviolet photolithography stripping solution are used in the subsequent processing; when electron beam resist is coated on the photolithography substrate, electron beam and electron beam etchant solution are used in the subsequent processing.
[0028] Preferably, the heating treatment in step (2) comprises heating treatment in a muffle furnace.
[0029] Preferably, the temperature of the muffle furnace heating treatment is 300-500°C, for example, 320°C, 340°C, 360°C, 380°C, 400°C, 420°C, 440°C, 460°C, 480°C, etc.
[0030] The present invention uses a muffle furnace at 300-500°C to separate the two-dimensional pattern robot and the metal oxide surface modified micro-magnetic control robot. If the temperature is too high, the magnetic material loses its magnetism due to high-temperature oxidation; if the temperature is too low, the various structural properties of the metal oxide surface, including the density of point defects, cannot be effectively changed, so that the synthesis of MOFs lacks connection points, and the obtained MOFs have poor performance. In addition, this temperature can carbonize the photoresist, and the two-dimensional structure robot and the substrate can be separated later.
[0031] Preferably, the rate at which the muffle furnace is heated to the heating treatment temperature is 5-15°C / min, for example, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min, 11°C / min, 12°C / min, 13°C / min, 14°C / min, etc.
[0032] Preferably, the muffle furnace heating treatment time is 4-8 hours, such as 5 hours, 6 hours, 7 hours, etc.
[0033] Preferably, the separating comprises ultrasonic shaking.
[0034] Preferably, the mass concentration of the organic ligand solution in step (2) is 10-20 mg / mL, such as 12 mg / mL, 14 mg / mL, 16 mg / mL, 18 mg / mL, etc.
[0035] Preferably, the solvent in the organic ligand solution includes any one of N-methylpyrrolidone (NMP), dimethylformamide (DMF), dimethylacetamide (DMAC), dimethyl sulfoxide (DMSO) or methanol (MeOH) or a combination of at least two thereof.
[0036] Preferably, the solvent in the organic ligand solution includes any one of a combination of N-methylpyrrolidone and methanol, a combination of dimethylformamide and methanol, a combination of dimethylacetamide and methanol, or a combination of dimethyl sulfoxide and methanol.
[0037] The reason why the solvent in the organic ligand solution of the present invention is preferably the above combination is that the metal oxide and the organic ligand can fully carry out coordination reaction in the preferred solvent, and can form MOFs membranes with different morphologies, thereby achieving effective adaptability to complex applications.
[0038] Preferably, the volume ratio of N-methylpyrrolidone and methanol is (1:9)-(9:1), for example, 1:9, 2:8, 3:7, 4:6, 5:5, 6:4, 7:3, 8:2 and 9:1, etc., preferably 1:9, 5:5, 6:4, 7:3, 8:2 or 9:1, and further preferably 1:9, 5:5 or 9:1.
[0039] Preferably, the volume ratio of dimethylformamide and methanol is (1:9)-(9:1), for example, 1:9, 2:8, 3:7, 4:6, 5:5, 6:4, 7:3, 8:2 and 9:1, etc., preferably 1:9, 2:8, 4:6, 5:5, 6:4, 7:3 or 8:2, and further preferably 1:9, 2:8 or 5:5.
[0040] Preferably, the volume ratio of dimethylacetamide and methanol is (1:9)-(9:1), for example 1:9, 2:8, 3:7, 4:6, 5:5, 6:4, 7:3, 8:2 and 9:1, etc., preferably 2:8, 3:7, 4:6, 5:5, 6:4, 7:3, 8:2 or 9:1, and further preferably 4:6, 5:5, 6:4 or 7:3.
[0041] Preferably, the volume ratio of dimethyl sulfoxide to methanol is (1:9)-(9:1), for example 1:9, 2:8, 3:7, 4:6, 5:5, 6:4, 7:3, 8:2 and 9:1, etc., preferably 1:9, 4:6, 5:5, 6:4, 7:3 or 8:2, and further preferably 1:9, 7:3 or 8:2.
[0042] Preferably, the temperature of the hydrothermal reaction in step (2) is 50-80°C, such as 55°C, 60°C, 65°C, 70°C, 75°C, etc.
[0043] The temperature of the hydrothermal reaction of the present invention is 50-80° C., within which the solvent is not likely to volatilize or undergo excessive pressure changes, thereby ensuring that the reaction proceeds mildly and effectively.
[0044] Preferably, the hydrothermal reaction time is 24-72 hours, such as 30 hours, 35 hours, 40 hours, 45 hours, 50 hours, 55 hours, 60 hours, 65 hours, 70 hours, etc. The present invention can complete the hydrothermal reaction in a shorter time.
[0045] Preferably, the post-treatment in step (2) specifically includes: using a magnet to enrich and fix the micro-magnetic control robot after the hydrothermal reaction, pouring out the solution of the system after the hydrothermal reaction, washing and drying, to obtain the micro-magnetic control robot.
[0046] Preferably, the washing comprises soaking with methanol.
[0047] Preferably, the soaking time is 0.5-1.5 h, for example 0.6 h, 0.8 h, 1.0 h, 1.2 h, 1.4 h, etc.
[0048] Preferably, the drying temperature is 120-180°C, such as 130°C, 140°C, 150°C, 160°C, 170°C, etc.
[0049] The drying temperature of the present invention is 120-180° C. Within this temperature range, the solvent can be fully volatilized and energy waste caused by excessively high temperature can be saved.
[0050] Preferably, the washing and drying are performed 3-5 times, for example 3 times, 4 times, 5 times, etc.
[0051] As a preferred technical solution, the preparation method comprises the following steps:
[0052] (1) coating a UV photoresist or an electron beam resist on a photolithography substrate, then exposing the substrate to ultraviolet light or an electron beam to design a robot, and finally developing the robot in a UV photolithography stripping solution or an electron beam etchant solution to obtain a two-dimensional patterned robot;
[0053] The surface of the two-dimensional pattern robot is coated with a first metal oxide layer, a first non-magnetic metal layer, a magnetic metal layer, a second non-magnetic metal layer and a second metal oxide layer in sequence by electron beam evaporation, magnetron sputtering evaporation or atomic deposition coating to obtain a metal oxide surface modified micro magnetron robot coated on the surface of the two-dimensional pattern robot;
[0054] (2) heating to 300-500° C. at a rate of 5-15° C. / min, isothermally treating for 4-8 hours, and after cooling, immersing the metal oxide surface-modified micro-magnetron robot in an organic ligand solution, and hydrothermally reacting at 50-80° C. for 24-72 hours to obtain a micro-magnetron robot coated on the surface of the substrate;
[0055] Then, the micro-magnetic robot is separated from the substrate surface by ultrasonic treatment;
[0056] Finally, the micro-magnetic control robot is enriched and fixed by a magnet, the solution of the system after the hydrothermal reaction is poured out, the micro-magnetic control robot is immersed and washed with methanol for 0.5-1.5 hours, the washing is repeated 3-5 times, and the micro-magnetic control robot is dried at 120-180° C. to obtain the micro-magnetic control robot.
[0057] In a third aspect, the present invention provides an application of the magnetically controlled robot described in the first aspect in a medical device.
[0058] Compared with the prior art, the present invention has the following beneficial effects:
[0059] The micro-magnetic control robot of the present invention can carry drugs by adsorption, has high carrying efficiency, and can also achieve effective adaptability to complex applications. The nitrogen content in the micro-magnetic control robot of the present invention is related to the selection and ratio of solvents in the preparation process. The higher the nitrogen content, the higher the proportion of MOFs and the higher the efficiency of drug delivery. By selecting solvents of different types and ratios, the resulting micro-magnetic control robot has different crystal structures and nitrogen contents, achieving effective adaptability to complex applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0060] Figure 1 is a schematic diagram of the surface microstructure of the micro-magnetically controlled robot described in Example 1;
[0061] Figure 2 is a schematic diagram of the surface microstructure of the micro-magnetically controlled robot described in Example 4;
[0062] Figure 3 is a schematic diagram of the surface microstructure of the micro-magnetically controlled robot described in Example 5;
[0063] Figure 4 is a schematic diagram of the surface microstructure of the micro-magnetically controlled robot described in Example 7;
[0064] Figure 5 is a schematic diagram of the surface microstructure of the micro-magnetically controlled robot described in Example 11;
[0065] Figure 6 is a schematic diagram of the surface microstructure of the micro-magnetically controlled robot described in Example 14;
[0066] Figure 7 is a schematic diagram of the surface microstructure of the micro-magnetically controlled robot described in Example 15;
[0067] Figure 8 is a schematic diagram of the surface microstructure of the micro-magnetically controlled robot described in Example 17;
[0068] Fig. 9 is a schematic diagram of the surface microstructure of the micro-magnetically controlled robot described in Example 21;
[0069] Fig.10 is a schematic diagram of the surface microstructure of the micro-magnetically controlled robot described in Example 24;
[0070] Fig.11 is a schematic diagram of the surface microstructure of the micro-magnetically controlled robot described in Example 25;
[0071] Fig.12 is a schematic diagram of the surface microstructure of the micro-magnetically controlled robot described in Example 27;
[0072] Fig.13 is a schematic diagram of the surface microstructure of the micro-magnetically controlled robot described in Example 31;
[0073] Fig.14 is a schematic diagram of the surface microstructure of the micro-magnetically controlled robot described in Example 34;
[0074] Fig.15 is a schematic diagram of the surface microstructure of the micro-magnetically controlled robot described in Example 35;
[0075] Fig.16 is a schematic diagram of the surface microstructure of the micro-magnetically controlled robot described in Example 37;
[0076] Fig.17 is a structural diagram of the micro-magnetically controlled robot described in Example 5 at an arc of 90°;
[0077] Fig.18 is an enlarged structural diagram of the micro-magnetically controlled robot described in Example 5 at an arc of 90°;
[0078] Fig.19 is a structural diagram of the micro-magnetically controlled robot described in Example 5 at an arc of 105°;
[0079] Fig. 20 is an enlarged structural diagram of the micro-magnetically controlled robot described in Example 5 at an arc of 105°;
[0080] Fig.21 is a structural diagram of the micro magnetically controlled robot described in Example 5 at an arc of 120°;
[0081] Fig. 22 is an enlarged structural diagram of the micro-magnetically controlled robot described in Example 5 at an arc of 120°;
[0082] Fig.23 is a structural diagram of the micro magnetically controlled robot described in Example 5 at an arc of 135°;
[0083] Fig.24 is an enlarged structural diagram of the micro-magnetically controlled robot described in Example 5 at an arc of 135°;
[0084] Fig.25 is a graph showing the relationship between the nitrogen content of the micro-magnetic control robot described in Example 1-41 and the volume ratio of two solvents in the organic ligand solution;
[0085] Fig.26 This is a scanning electron microscope image of the drug coverage of the micro-magnetically controlled robot described in Example 2. DETAILED DESCRIPTION
[0086] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0087] Example 1
[0088] This embodiment provides a micro-magnetic control robot, which includes a magnetic metal layer and a metal organic skeleton layer coated on the surface of the magnetic metal layer;
[0089] The raw materials for preparing the metal organic framework layer include metal oxide (ZnO) and organic ligand (2-methylimidazole).
[0090] The method for preparing the micro magnetically controlled robot comprises the following steps:
[0091] (1) A silicon wafer was used as a photolithography substrate, which was immersed in acetone and ultrasonically treated for 10 minutes, then repeatedly washed with isopropanol and deionized water, and finally dried at 120° C. A uniform photoresist layer with a thickness of 5 μm was deposited on the photolithography substrate using a spin coater (the photoresist was purchased from Merck (Xi'an Boyan Micro-Nano Information Technology Co., Ltd.) and the brand was The photoresist layer was then pre-baked at 110°C for 90 seconds. Then, a dark-field mask with a microrobot design (created using AutoCAD) was used to UV-lithograph the pattern onto the photoresist by UV exposure (mask aligner, SUSS MA6), followed by a hard bake at 110°C for 90 seconds. Next, the pattern was developed in a developer for 4 minutes, and after development, it was hard-baked continuously at 120°C for 20 minutes to obtain a two-dimensional pattern robot on the sacrificial layer of the photoresist.
[0092] A 450nm first ZnO film was deposited on the photoresist layer using a confocal RF magnetron sputtering coating system (KYKY-500CK-500ZF, equipped with a 4-inch zinc oxide composite target (Beijing Youhao Metal, 99.9%), and the sample was mounted on a 6-inch alloy substrate. The two-dimensional pattern robot of the photoresist sacrificial layer was deposited at 30°C, a sputtering gas pressure of 1.33Pa, and an argon gas flow rate of 50sccm (RF power: 150W). The base pressure of the samples was higher than 20μPa. The rotation speed of the alloy substrate was set to 18rpm to obtain a uniform deposition thickness;
[0093] Al, Ni, and Al thin films with thicknesses of 10 nm, 100 nm, and 10 nm were deposited on the ZnO thin film in sequence by electron beam vacuum evaporation (HHV coating unit: TF500). The pressure in the vacuum chamber was maintained at 2×10 -6 mbar, and monitored using digital Pirani and Penning pressure gauges; the deposition rate and film thickness were measured using a quartz monitor, where the deposition rates of the two Al layers and the Ni layer were and
[0094] A second ZnO film with a thickness of 450 nm is deposited on the aluminum layer using the same sputtering process and conditions as the first ZnO film, thereby obtaining the metal oxide surface-modified micro-magnetic control robot coated on the surface of the two-dimensional pattern robot;
[0095] (2) placing the microrobot in a muffle furnace, setting the heating rate of the muffle furnace to 10°C / min, the treatment temperature to 440°C, the isothermal time to 5h, and cooling to room temperature;
[0096] Then, 5 mL of NMP, 45 mL of MeOH and 1 g of 2-methylimidazole were mixed to obtain an organic ligand solution, and the metal oxide surface modified micro-magnetron robot was immersed in the organic ligand solution, and a hydrothermal reaction was performed at 65° C. for 64 h, and ultrasonic mixing was performed for 2 minutes to separate the photolithography substrate and the metal oxide surface modified micro-magnetron robot;
[0097] Finally, the micro-magnetic control robot was enriched and fixed by a magnet, the solution of the system after the hydrothermal reaction was poured out, the micro-magnetic control robot was soaked in methanol for 1 hour for washing, and dried at 150°C. The washing and drying were repeated 3 times to obtain the micro-magnetic control robot (MOFs-based micro-magnetic control robot based on ZIF-8).
[0098] Embodiment 2-9
[0099] The difference between Example 2-9 and Example 1 is that the volume ratios of NMP and MeOH in the organic ligand solution are 2:8, 3:7, 4:6, 5:5, 6:4, 7:3, 8:2 and 9:1, respectively, and the total volume of the two is 50 mL. The rest of Examples 2-9 are the same as Example 1.
[0100] Example 10
[0101] The difference between Example 10 and Example 1 is that the solvent of the organic ligand solution is 50 mL of NMP, that is, the volume ratio of NMP to MeOH is 10:0, and the rest is the same as Example 1.
[0102] Embodiment 11
[0103] This embodiment provides a micro-magnetic control robot, which includes a magnetic metal layer and a metal organic skeleton layer coated on the surface of the magnetic metal layer;
[0104] The raw materials for preparing the metal organic framework layer include metal oxide (ZnO) and organic ligand (2-methylimidazole).
[0105] The method for preparing the micro magnetically controlled robot comprises the following steps:
[0106] (1) A silicon wafer was used as a photolithography substrate, which was immersed in acetone and ultrasonically treated for 10 minutes, then repeatedly washed with isopropanol and deionized water, and finally dried at 150° C. A uniform photoresist layer with a thickness of 2 μm was deposited on the photolithography substrate using a spin coater (the photoresist was purchased from Microchem (agent of Xi'an Boyan Micro-Nano Information Technology Co., Ltd.), with a brand of The photoresist layer was then pre-baked at 65°C for 60 seconds and then at 95°C for 90 seconds. Then, a dark-field mask with a microrobot design (created using AutoCAD) was used to UV-lithograph the pattern onto the photoresist by UV exposure (mask aligner, SUSSMA6), followed by hard baking at 95°C for 90 seconds. Next, the pattern was developed in a developer for 30 seconds, and after development, it was continuously hard-baked at 120°C for 20 minutes to obtain a two-dimensional pattern robot of the photoresist sacrificial layer.
[0107] A 200nm first ZnO film was deposited on the photoresist layer using a confocal RF magnetron sputtering coating system (KYKY-500CK-500ZF, equipped with a 4-inch zinc oxide composite target (Beijing Youhao Metal, 99.9%), and the sample was mounted on a 6-inch alloy substrate). The two-dimensional pattern robot of the photoresist sacrificial layer was deposited at 30°C, a sputtering gas pressure of 1.33Pa, and an argon gas flow rate of 50sccm (RF power: 150W). The base pressure of the samples was higher than 20μPa. The rotation speed of the alloy substrate was set to 18rpm to obtain a uniform deposition thickness;
[0108] Al, Ni, and Al thin films with thicknesses of 10 nm, 100 nm, and 10 nm were deposited on the ZnO thin film in sequence by electron beam vacuum evaporation (HHV coating unit: TF500). The pressure in the vacuum chamber was maintained at 2×10 -6 mbar, and monitored using digital Pirani and Penning pressure gauges; the deposition rate and film thickness were measured using a quartz monitor, where the deposition rates of the two Al layers and the Ni layer were and
[0109] A second ZnO film with a thickness of 200 nm is deposited on the aluminum layer using the same sputtering process and conditions as the first ZnO film, thereby obtaining the metal oxide surface-modified micro-magnetic control robot coated on the surface of the two-dimensional pattern robot;
[0110] (2) placing the microrobot in a muffle furnace, setting the heating rate of the muffle furnace to 10°C / min, the treatment temperature to 415°C, the isothermal time to 5h, and cooling to room temperature;
[0111] Then, 5 mL of DMAC, 45 mL of MeOH and 2 g of 2-methylimidazole were mixed to obtain an organic ligand solution, and the metal oxide surface modified micro-magnetron robot was immersed in the organic ligand solution, and a hydrothermal reaction was performed at 65° C. for 48 h, and ultrasonic mixing was performed for 10 minutes, and the photolithography substrate and the metal oxide surface modified micro-magnetron robot were separated;
[0112] Finally, the micro-magnetic control robot was enriched and fixed by a magnet, the solution of the system after the hydrothermal reaction was poured out, the micro-magnetic control robot was soaked in methanol for 1 hour for washing, and dried at 150°C. The washing and drying were repeated 3 times to obtain the micro-magnetic control robot (MOFs-based micro-magnetic control robot based on ZIF-8).
[0113] Examples 12-19
[0114] The difference between Examples 12-19 and Example 11 is that the volume ratios of DMAC and MeOH in the organic ligand solution are 2:8, 3:7, 4:6, 5:5, 6:4, 7:3, 8:2 and 9:1, respectively, and the rest of Examples 12-19 are the same as Example 11.
[0115] Embodiment 20
[0116] The difference between Example 20 and Example 11 is that the solvent in the organic ligand solution is 50 mL of DMAC, that is, the volume ratio of DMAC to MeOH is 10:0, and the rest is the same as Example 11.
[0117] Embodiment 21
[0118] This embodiment provides a micro-magnetic control robot, which includes a magnetic metal layer (Ni) and a metal organic framework layer coated on the surface of the magnetic metal layer;
[0119] The raw materials for preparing the metal organic framework layer include metal oxide (ZnO) and organic ligand (2-methylimidazole).
[0120] The method for preparing the micro magnetically controlled robot comprises the following steps:
[0121] (1) A silicon wafer was used as a photolithography substrate, which was immersed in acetone and ultrasonically treated for 10 minutes, then repeatedly washed with isopropanol and deionized water, and finally dried at 150° C. A uniform photoresist layer with a thickness of 2 μm was deposited on the photolithography substrate using a spin coater (the photoresist was purchased from Microchem (agent of Xi'an Boyan Micro-Nano Information Technology Co., Ltd.), with a brand of The photoresist layer was then pre-baked at 95°C for 90 seconds. Then, a dark-field mask with a microrobot design (created using AutoCAD) was used to UV-lithograph the pattern onto the photoresist by UV exposure (mask aligner, SUSS MA6), followed by a hard bake at 95°C for 90 seconds. Next, the pattern was exposed to UV light for 45 seconds, and then developed in a developer for 60 seconds. After development, the pattern was hard-baked continuously at 120°C for 20 minutes to obtain a two-dimensional pattern robot with a sacrificial photoresist layer.
[0122] A 50nm first ZnO film was deposited on the photoresist layer using a confocal RF magnetron sputtering coating system (KYKY-500CK-500ZF, equipped with a 4-inch zinc oxide composite target (Beijing Youhao Metal, 99.9%), and the sample was mounted on a 6-inch alloy substrate). The two-dimensional pattern robot of the photoresist sacrificial layer was deposited at 30°C, a sputtering pressure of 1.33Pa, and an argon flow rate of 50sccm (RF power: 150W). The base pressure of the samples was higher than 20μPa. The rotation speed of the alloy substrate was set to 18rpm to obtain a uniform deposition thickness;
[0123] Electron beam vacuum evaporation (HHV coating unit: TF500) was used to deposit Ni thin films with a thickness of 100 nm on the ZnO thin films. The pressure in the vacuum chamber was maintained at 2×10 -6 mbar and monitored using digital Pirani and Penning pressure gauges; deposition rate and film thickness were measured with a quartz monitor;
[0124] A second ZnO film of 50 nm is deposited on the Ni layer using the same sputtering process and conditions as the first ZnO film, to obtain the metal oxide surface-modified micro-magnetic control robot coated on the surface of the two-dimensional pattern robot;
[0125] (2) placing the microrobot in a muffle furnace, setting the heating rate of the muffle furnace to 10°C / min, the treatment temperature to 415°C, the isothermal time to 5h, and cooling to room temperature;
[0126] Then, 5 mL of DMSO, 45 mL of MeOH and 2 g of 2-methylimidazole were mixed to obtain an organic ligand solution, and the metal oxide surface modified micro-magnetron robot was immersed in the organic ligand solution, and a hydrothermal reaction was performed at 65° C. for 48 h, and ultrasonic mixing was performed for 10 minutes to separate the photolithography substrate and the metal oxide surface modified micro-magnetron robot;
[0127] Finally, the micro-magnetic control robot was enriched and fixed by a magnet, the solution of the system after the hydrothermal reaction was poured out, the micro-magnetic control robot was soaked in methanol for 1 hour for washing, and dried at 150°C. The washing and drying were repeated 5 times to obtain the micro-magnetic control robot (MOFs-based micro-magnetic control robot based on ZIF-8).
[0128] Examples 22-29
[0129] The difference between Examples 22-29 and Example 21 is that the volume ratios of DMSO and MeOH in the organic ligand solution are 2:8, 3:7, 4:6, 5:5, 6:4, 7:3, 8:2 and 9:1 respectively, and the total volume of the two solvents is 50 mL. The rest of Examples 22-29 are the same as Example 21.
[0130] Embodiment 30
[0131] The difference between Example 30 and Example 21 is that the solvent in the organic ligand solution is 50 mL of DMSO, that is, the volume ratio of DMSO to MeOH is 10:0, and the rest is the same as Example 21.
[0132] Examples 31-39
[0133] The difference between Examples 31-39 and Example 1 is that the types (combination of DMF and MeOH) and volume ratios of the two solvents in the organic ligand solution are different, and the total volume of the two solvents is 50 mL;
[0134] The volume ratios of DMF and MeOH solvents in the organic ligand solutions of Examples 31-39 are 1:9, 2:8, 3:7, 4:6, 5:5, 6:4, 7:3, 8:2 and 9:1, respectively. The rest of Examples 31-39 are the same as Example 1.
[0135] Embodiment 40
[0136] The difference between Example 40 and Example 31 is that the solvent in the organic ligand solution is 50 mL of DMF, that is, the volume ratio of DMF to MeOH is 10:0, and the rest is the same as Example 31.
[0137] Embodiment 41
[0138] The difference between this embodiment and embodiment 1 is that the solvent in the organic ligand solution is 50 mL of MeOH, and the rest is the same as embodiment 1.
[0139] Comparative Example 1
[0140] The difference between this comparative example and Example 1 is that the micro-magnetic control robot is a carrying type, and the micro-magnetic control robot is formed by a magnetic metal salt (zinc nitrate) and an organic ligand (2-methylimidazole).
[0141] The preparation method of the micro magnetic control robot comprises the following steps:
[0142] The metal salt and the organic ligand are mixed into an organic solvent system in a molar ratio of 1:2, and the hydrothermal reaction temperature is 80°C for 4 days. After drying, the micro-magnetic control robot is obtained by a physical adhesion method to the surface of the two-dimensional structure robot.
[0143] Comparative Example 2
[0144] The micro-magnetically controlled robot in this comparative example is shown in DOI: 10.1002 / adma.201901592, and the scanning electron microscope image of the drug coverage of the micro-magnetically controlled robot is shown in Fig.26 As shown in (ZIF-8 magnetically controlled robot Figure 3a).
[0145] Performance Testing
[0146] The micro-magnetically controlled robots described in Examples 1-41 were subjected to the following scanning electron microscope tests, and the test results are summarized in Figure 1-25 middle.
[0147] Analysis of Comparative Example 1 and Example 1 shows that the preparation method of Comparative Example 1 is more difficult to implement, and the physical adhesion method makes it difficult to carry the drug, which proves the unique advantage of using the micro-magnetically controlled robot of the present invention in the preparation process.
[0148] Analysis of Comparative Example 2 and Example 1 shows that the coverage of the drug of the micro-magnetically controlled robot described in Comparative Example 2 is as follows: Fig.26 The figure shown is clearly too low.
[0149] analyze Figure 1-4 It can be seen that Figure 1 The MOFs shown show micron-scale grain size, full and dense crystal form, and extremely high coverage; Figure 2 The MOFs shown exhibit nanoscale grain size and high coverage; Figure 3 The MOFs shown are in the form of dense sheets; Figure 4 The MOFs shown are in the form of dense sheets.
[0150] analyze Figure 5-8 It can be seen that Figure 5 The MOFs shown are cylindrical to droplet-shaped with general uniformity; Figure 6 The MOFs shown show micron-scale grain size, full and dense crystal form, and high coverage; Figure 7 The MOFs shown have micron-level crystal size, full and dense crystal form, and high coverage; Figure 8 The MOFs shown have micron-scale grain size, full and dense crystal structure and high coverage.
[0151] analyze Figure 9-12 It can be seen that Fig. 9 The MOFs shown show micron-scale grain size, full and dense crystal form, and average coverage; Fig.10 The MOFs shown have micron-sized grain sizes and average coverage; Fig.11 The MOFs shown have nanoscale grain size and average coverage; Fig.12 The MOFs shown are in the form of dense sheets.
[0152] analyze Figure 13-16 It can be seen that Fig.13 The MOFs shown have micron-scale grain size, full and dense crystal form, and average coverage; Fig.14 The MOFs shown have micron-scale grain size, irregular crystal shape, and average coverage; Fig.15 The MOFs shown are spherical to droplet-shaped, with good crystal uniformity and average coverage; Fig.16The MOFs shown have nanoscale grain size and average coverage.
[0153] analyze Figure 17-24 It can be seen that the surface of the micro-magnetic control robot described in the present invention is loose and porous, and its application can be realized under different curvatures.
[0154] analyze Fig.25 It can be seen that the nitrogen content in the micro-magnetic control robot of the present invention is related to the selection and ratio of the solvent in the preparation process. The higher the nitrogen content, the higher the proportion of MOFs and the higher the efficiency of drug delivery. For NMP, the volume ratio of NMP to MeOH is 1:9, 5:5, 6:4, 7:3, 8:2 or 9:1, and the obtained micro-magnetic control robot has a higher nitrogen content, especially 1:9, 5:5 or 9:1; for DMAC, the volume ratio of DMAC to MeOH is 2:8, 3:7, 4:6, 5:5, 6:4, 7:3, 8:2 or 9:1, and the obtained micro-magnetic control robot has a higher nitrogen content, especially 4:6, 5:5, 6:4 or 7:3; for DMSO, the volume ratio of DMSO to MeOH is 1:9, 4:6, 5:5, 6:4, 7:3 or 8:2, and the resulting micro-magnetic control robot has a higher nitrogen content, especially 1:9, 7:3 or 8:2; for DMF, the volume ratio of DMF to MeOH is 1:9, 2:8, 4:6, 5:5, 6:4, 7:3 or 8:2, and the resulting micro-magnetic control robot has a higher nitrogen content, especially 1:9, 2:8 or 5:5.
[0155] The applicant declares that the present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a micro magnetically controlled robot, characterized in that: The preparation method comprises the following steps: (1) coating a two-dimensional pattern robot on the upper surface of a substrate, and then sequentially coating a first metal oxide layer, a first non-magnetic metal layer, a magnetic metal layer, a second non-magnetic metal layer, and a second metal oxide layer on the upper surface of the two-dimensional pattern robot to obtain a metal oxide surface-modified micro-magnetic robot coated on the surface of the substrate; (2) The metal oxide surface modified micro-magnetron robot coated on the substrate surface is subjected to a heating treatment, and after cooling, it is immersed in an organic ligand solution for a hydrothermal reaction to obtain a two-dimensional pattern micro-magnetron robot coated on the substrate surface, and then the two-dimensional pattern micro-magnetron robot is separated from the substrate surface and post-processed to obtain the micro-magnetron robot.
2. The preparation method according to claim 1, characterized in that: The thickness of the metal oxide layer in step (1) is greater than 25 nm.
3. The preparation method according to claim 1, characterized in that: The coating includes any one of electron beam evaporation, magnetron sputtering evaporation, electrochemical deposition, thermal evaporation or atomic deposition coating.
4. The preparation method according to claim 1, characterized in that: The preparation method of the two-dimensional pattern robot includes: coating ultraviolet photoresist or electron beam resist on a photolithography substrate, exposing it to ultraviolet light or electron beam, designing the robot according to the structure of the micro-magnetic robot, and then developing it in ultraviolet photolithography stripping solution or electron beam etchant solution to obtain the two-dimensional pattern robot.
5. The preparation method according to claim 1, characterized in that: The heating treatment in step (2) includes heating treatment using a muffle furnace.
6. The preparation method according to claim 5, characterized in that: The temperature of the muffle furnace heating treatment is 300-500°C.
7. The preparation method according to claim 5, characterized in that: The rate at which the muffle furnace is heated to the heating treatment temperature is 5-15°C / min.
8. The preparation method according to claim 5, characterized in that: The time of the muffle furnace heating treatment is 4-8 hours.
9. The preparation method according to claim 1, characterized in that: The separation includes ultrasonic vibration.
10. The preparation method according to claim 1, characterized in that: The mass concentration of the organic ligand solution in step (2) is 10-20 mg / mL.
11. The preparation method according to claim 1, characterized in that: The solvent in the organic ligand solution includes any one of N-methylpyrrolidone, dimethylformamide, dimethylacetamide, dimethyl sulfoxide or methanol, or a combination of at least two thereof.
12. The preparation method according to claim 1, characterized in that: The solvent in the organic ligand solution includes any one of a combination of N-methylpyrrolidone and methanol, a combination of dimethylformamide and methanol, a combination of dimethylacetamide and methanol, or a combination of dimethyl sulfoxide and methanol.
13. The preparation method according to claim 12, characterized in that: The volume ratio of the N-methylpyrrolidone to methanol is (1:9)-(9:1).
14. The preparation method according to claim 13, characterized in that: The volume ratio of the N-methylpyrrolidone to methanol is 1:9, 5:5, 6:4, 7:3, 8:2 or 9:
1.
15. The preparation method according to claim 12, characterized in that: The volume ratio of dimethylformamide to methanol is (1:9)-(9:1).
16. The preparation method according to claim 15, characterized in that: The volume ratio of dimethylformamide to methanol is 1:9, 2:8, 4:6, 5:5, 6:4, 7:3 or 8:
2.
17. The preparation method according to claim 12, characterized in that: The volume ratio of dimethylacetamide to methanol is (1:9)-(9:1).
18. The preparation method according to claim 17, characterized in that: The volume ratio of dimethylacetamide to methanol is 2:8, 3:7, 4:6, 5:5, 6:4, 7:3, 8:2 or 9:
1.
19. The preparation method according to claim 12, characterized in that: The volume ratio of dimethyl sulfoxide to methanol is (1:9)-(9:1).
20. The preparation method according to claim 19, characterized in that: The volume ratio of dimethyl sulfoxide to methanol is 1:9, 4:6, 5:5, 6:4, 7:3 or 8:
2.
21. The preparation method according to claim 1, characterized in that: The temperature of the hydrothermal reaction in step (2) is 50-80°C.
22. The preparation method according to claim 1, characterized in that: The hydrothermal reaction time is 24-72h.
23. The preparation method according to claim 1, characterized in that: The post-treatment in step (2) specifically includes: using a magnet to enrich and fix the two-dimensional pattern micro-magnetic control robot after the hydrothermal reaction, pouring out the solution of the system after the hydrothermal reaction, washing, and drying to obtain the micro-magnetic control robot.
24. The preparation method according to claim 23, characterized in that: The washing includes soaking with methanol.
25. The preparation method according to claim 24, characterized in that: The soaking time is 0.5-1.5h.
26. The preparation method according to claim 23, characterized in that: The drying temperature is 120-180°C.
27. The preparation method according to claim 23, characterized in that: The washing is performed 3-5 times.
28. The preparation method according to claim 1, characterized in that: The preparation method comprises the following steps: (1) coating a UV photoresist or an electron beam resist on a photolithography substrate, then exposing the substrate to ultraviolet light or an electron beam to design a robot, and finally developing the robot in a UV photolithography stripping solution or an electron beam etchant solution to obtain a two-dimensional patterned robot; The surface of the two-dimensional pattern robot is coated with a first metal oxide layer, a first non-magnetic metal layer, a magnetic metal layer, a second non-magnetic metal layer, and a second metal oxide layer in sequence by electron beam evaporation, magnetron sputtering evaporation or atomic deposition coating to obtain a metal oxide surface modified micro magnetron robot coated on the surface of the two-dimensional pattern robot; (2) heating the substrate to 300-500° C. at a rate of 5-15° C. / min, isothermally treating the substrate for 4-8 hours, and after cooling, immersing the metal oxide surface modified micro-magnetron robot in an organic ligand solution, and hydrothermally reacting the micro-magnetron robot at 50-80° C. for 24-72 hours to obtain a two-dimensional pattern micro-magnetron robot coated on the substrate surface; Then, the two-dimensional patterned micro-magnetic robot is separated from the substrate surface by ultrasonic treatment; Finally, the two-dimensional pattern micro-magnetic robot is enriched and fixed by a magnet, the solution of the system after the hydrothermal reaction is poured out, the two-dimensional pattern micro-magnetic robot is immersed and washed with methanol for 0.5-1.5 hours, the washing is repeated 3-5 times, and the micro-magnetic robot is dried at 120-180°C to obtain the micro-magnetic robot.
29. A micro-magnetic control robot manufactured according to the method for manufacturing a micro-magnetic control robot according to any one of claims 1 to 28, characterized in that: The micro magnetic control robot comprises a metal oxide layer, a magnetic metal layer and a metal organic skeleton layer which are stacked in sequence; non-magnetic metal layers are arranged on both sides of the magnetic metal layer; The metal organic framework layer is obtained by coordination of metal oxide and organic ligand through hydrothermal reaction.
30. The micro magnetically controlled robot according to claim 29, characterized in that: The metal oxide includes zinc oxide.
31. The micro magnetically controlled robot according to claim 29, characterized in that: The organic ligand includes 2-methylimidazole.
32. The micro magnetically controlled robot according to claim 29, characterized in that: The magnetic metal layer includes any one of nickel, cobalt, samarium cobalt, ferrosoferric oxide or neodymium iron boron, or a combination of at least two thereof.
33. The micro magnetically controlled robot according to claim 29, characterized in that: The non-magnetic metal layer includes an aluminum layer.
34. Application of a magnetically controlled robot obtained by the method for preparing a micro-magnetically controlled robot according to any one of claims 1 to 28 in medical devices.
Citation Information
Patent Citations
Micro magnetic control robot, preparation methods of inner core and film, and assembly method of micro magnetic control robot,
CN111493973A
T4 bacteriophage-imitated targeted drug delivery micro magnetic control robot and control method thereof
CN111921072A
Magnetic nano-pore metal-organic framework core-shell material preparation, functionalized design, and application.
CN103203207A
Miniature magnetic control robot
CN216608995U